2015
DOI: 10.1093/hmg/ddv314
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic LRRK2 mutations, through increased kinase activity, produce enlarged lysosomes with reduced degradative capacity and increase ATP13A2 expression

Abstract: Lysosomal dysfunction plays a central role in the pathogenesis of several neurodegenerative disorders, including Parkinson's disease (PD). Several genes linked to genetic forms of PD, including leucine-rich repeat kinase 2 (LRRK2), functionally converge on the lysosomal system. While mutations in LRRK2 are commonly associated with autosomal-dominant PD, the physiological and pathological functions of this kinase remain poorly understood. Here, we demonstrate that LRRK2 regulates lysosome size, number and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
172
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(195 citation statements)
references
References 88 publications
15
172
0
1
Order By: Relevance
“…The most common pathological mutation of LRRK2 (G2019S) causes a phenotype exhibiting lysosomal expansion and diminished lysosomal degradation of substrate. This phenotype is dependent on the catalytic activity of LRRK2 (Henry et al, 2015). The G2019S mutation also leads to decreased lysosomal pH and impaired cathepsin function, as well as increased expression of the lysosomal ATPase ATP13A2 in brains from mouse and human LRRK2 G2019S carriers (Henry et al, 2015), possibly as a compensatory response.…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The most common pathological mutation of LRRK2 (G2019S) causes a phenotype exhibiting lysosomal expansion and diminished lysosomal degradation of substrate. This phenotype is dependent on the catalytic activity of LRRK2 (Henry et al, 2015). The G2019S mutation also leads to decreased lysosomal pH and impaired cathepsin function, as well as increased expression of the lysosomal ATPase ATP13A2 in brains from mouse and human LRRK2 G2019S carriers (Henry et al, 2015), possibly as a compensatory response.…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
“…This phenotype is dependent on the catalytic activity of LRRK2 (Henry et al, 2015). The G2019S mutation also leads to decreased lysosomal pH and impaired cathepsin function, as well as increased expression of the lysosomal ATPase ATP13A2 in brains from mouse and human LRRK2 G2019S carriers (Henry et al, 2015), possibly as a compensatory response. Notably, in a c. elegans tauopathy model, LRRK2 mutations lead to HNE modification of the subunits V1A and V1B of v-ATPase (Di Domenico et al, 2012), reminiscent of the oxidative modifications of v-ATPase in AD and DS.…”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
“…It is important to note that while the pSer935 site may reflect LRRK2 kinase inhibition, it is an indirect measure of LRRK2 kinase activity and expected phosphorylation of substrates. So far in model systems, pSer935 has mirrored the dephosphorylation of the LRRK2 substrate pSer1292 and pRab (Fraser et al, 2016a; Henry et al, 2015; Steger et al, 2016). …”
Section: Biomarkers For Lrrk2 Inhibition and Therapeutic Windows Fmentioning
confidence: 99%
“…Mutant LRRK2 has been shown to cause lysosome/autophagic pathway impairment (Alegre-Abarrategui and Wade-Martins, 2009; Henry et al, 2015; Esteves and Cardoso, 2016). A recent study has identified that LRRK2 mutations lead to an increase in lysosomal size and a decrease in their ability for degradation (Bandyopadhyay et al, 2014), as well as impairs the autophagic cycle's ability to clear toxic proteins (Alegre-Abarrategui and Wade-Martins, 2009; Esteves and Cardoso, 2016).…”
Section: Discussionmentioning
confidence: 99%